Beyond Four-Walled Campuses: Models of Ecumenical Theological Education in Interfaith Issues in India - Longchar, A. Wati (International review of mission, 2009)
This article examines the relevancy of three education system models – professional or university, banking or teacher-centred, and campus or residential – from an inter-religious perspective. These models are no longer adequate in a multi-religious context and a shift is imperative. We need to evolve a model of education “together with people”, which includes all sections of the society – rich and poor, young and old, Christians and non-Christians. An inclusive curriculum that affirms plurality/diversity and the common good is urgently needed. This must take place within the larger academic world. A theological education in interaction with the secular learning process will contribute to reinforcing moral and ethical values in society for the common good.